Development of a PostGIS-based method for creating risk maps of natural disasters using the example of Georgia - Natsvlishvili, Levan; Jorjiashvili, Nato; Kochoradze, Vakhtang (Geodesy and Cartography, 2022)
This article discusses a method for creating a risk map of natural disasters for a specific area using PostGIS analysis. This method, which is described in detail, is based entirely on the use of open-source programs and spatial SQL directives. It is designed to use widely available GIS programs to create a flexible method that performs operations on OGC geometry. The area to be analyzed is covered with a polygonal grid. The size of the polygon is determined by the size of the study area. For each element of the grid (polygon), attribute values are determined for the traits characteristic of the area: seismic, landslide, mudflow, rockfall, population density, and number of buildings. The attribution values for geometry are assigned based on PostGIS analysis. The process of creating a risk map involves the summation of different hazard maps. Our method’s originality lies in the fact that the initial data is transformed so that it is possible to carry out map algebra operations with vector data. The method is designed to create risk maps based on OGC vector data analysis, which will help experts and stakeholders working on risk assessment and decision-making to develop a risk management strategy.